Efektivitas Kriteria Restrukturisasi Dalam Meningkatkan Kualitas Portofolio Pembiayaan - Hendy Herijanto; Restu Wulandari (STES Islamic Village, 2016)
This study aims(1) to know customer financing areconsider want-not want and capable-incapable on Unit UsahaSyariah PT. Bank Tabungan Negara (2) to know the criteria ofthe restructuring which occur on Unit Usaha Syariah PT. BankTabungan Negara, and (3) to ensure that the criteria that havea positive impact on improving the financing portfolio on UnitUsaha Syariah PT. Bank Tabungan Negara. To achieve theseobjectives, the author uses qualitative research methodology inthis is field research. Sources of data obtained directly from thestudy site on Unit Usaha Syariah PT. Bank Tabungan Negara fromdocuments relating to the cases studied. In addition, the dataobtained from direct interviews with Departement HeadRestructuring and Recovery Collection and Workout ShariaDivision dan Restructuring and Recovery Collection and WorkoutOfficer Sharia Division. After the data were completely collected,the author analyzed the data by descriptive analysis, using thedeductive analysis method, in which a specific conclusion is madefrom general data that have been collected. After conducting theresearch, it is concluded that (1) Bank in determining thecustomers want-not want is from the response of the customerafter receiving first to third a warning letter, while in determiningthe customer is capable-incapable were determined by theaccuracy of the promise to pay the arrears that have been agreed.(2) There are 5 (five) criteria restructuring on UUS BTN ie: hospitalfees, education fees of children, fixed income but needs increase,layoffs but had returned to work, and a decrease in revenues. Thewhole reason is temporary, kasuistis, and the positive reasons thatthese criteria may be considered for approval. (3) When measuredfor one year from the restructuring provision, criteria ofrestructuring customers collectibility are still acceptable orhighest Dalam Perhatian Khsusus (DPK) so that said effective.